Case report: A rare case of left ventricular noncompaction in two Chinese siblings with becker muscular dystrophy caused by deletion of exons 10 to 12 in the DMD gene - Li, Jingdong; Zhu, Wanyue; Su, Guanhua; Zhu, Feng; Shuai, Xinxin; Meng, Yidi; Zhang, Jiaming; Chen, Hao (Frontiers in Cardiovascular Medicine, 2023)
Background: Becker muscular dystrophy (BMD) is an inherited X-linked recessive condition resulting from mutations of the DMD gene encoding dystrophin. Left ventricular noncompaction (LVNC) is a rare cardiomyopathy morphologically characterized by abnormal myocardial trabeculae and deep recesses in the left ventricle. LVNC in BMD patients has only rarely been reported.In the present study, we identified a deletion mutation in exons 10 to 12 (EX10_12 del) of the DMD gene (reference sequence NM_004006.2) in two Chinese siblings with BMD and LVNC by high throughput targeted next-generation sequencing (NGS) and quantitative polymerase chain reaction (qPCR). The proband was a 22-year-old man admitted with dyspnea, abdominal distention, and polyserositis. It is noteworthy that both the proband and his younger brother manifested progressive muscular atrophy and creatine kinase (CK) elevation. Light and electron microscopy examination of muscle biopsies showed the typical features of dystrophinopathies. Cardiac magnetic resonance imaging and echocardiography demonstrated that both brothers had an enlarged left ventricle, LVNC, and reduced left ventricular ejection fraction. Finally, the proband underwent heart transplantation at age 26 with an event-free follow-up over 4 years post-transplantation.This case further enriches our knowledge of the symptoms, genotype, cardiac performance, management, and prognosis of BMD patients complicated by LVNC. It is recommended that early comprehensive cardiac evaluation should be considered for patients with BMD to exclude LVNC, as this may have a significant impact on their prognosis.